Analysis of Characteristics, Causes and Countermeasures of the Heavy MetalPollution in the Middle and Upper Reaches of the Diaojiang River Basin - LI Donglin; PENG Bin; LIANG Mei; LU Shangxu; WEI Hailing (Renmin Zhujiang)
The combination of water quality and flow monitoring is an important direction for thefuture development of the hydrological monitoring system. Based on the modified Tomlinsonpollution load index evaluation model, this paper arranges 10 sampling sites including TanghanVillage etc. in the middle and upper reaches of the Diaojiang River Basin in the non-flood seasonof 2018 to monitor and survey the quantity and quality of 8 kinds of heavy metal pollutants suchas copper, zinc, arsenic, mercury, cadmium, lead, manganese and antimony synchronously, andanalyzes the causes of pollution and proposes countermeasures by comparing the variation ofpollution characteristics and pollution load indexes before and after the modification of theevaluation model. The results show that the Tomlinson pollution load index evaluation modelmodified by introducing the corresponding water flow Q could fully reveal the coupled pollutionseverity of the heavy metal pollution under the condition of a low concentration and a high flow,which has great theoretical and practical significance for the accurate identification andscientific prevention & control of the heavy metal pollution in the Diaojiang River Basin.